STUDI LITERATUR ANALISIS EFEK SAMPING OBAT PADA PASIEN TUBERKULOSIS - Siti Rahmah; Herda Ariyani; Dedi Hartanto (LPPM - Universitas Muhammadiyah Banjarmasin, 2021)
Tuberculosis is a contagious disease caused by the bacteria Mycobacterium tuberculosis. The cause of tuberculosis treatment is often unsuccessful due to the emergence of drug side effects, which makes patients who experience drug side effects not adhering to treatment. This study aims to determine and identify any side effects that occur during treatment with OAT in tuberculosis patients. The research method used is literature study. The results showed that on average women who experienced drug side effects were women than men. The largest percentage of the body's organ systems that experience drug side effects are gastrointestinal, and the skin is the most common cause of adverse reactions. Common and dominant types of manifestations of drug side effects are nausea, itching, and lethargy. The majority of the score categories in this study obtained were in the